Auditor Professional Ethics in the Post Modern Paradigm towards Sustainable Financial Report Audits - Napitupulu, Bertha Elvy; Djaddang, Syahril (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This research addresses the role of auditors' professional ethics in the context of sustainability auditing in the post-modern era, where social and technological changes impact the accountability and transparency of corporate financial statements. Auditors serve not only as financial statement watchdogs but also as strategic advisors who assist companies in managing risks, complying with sustainability standards, and maintaining stakeholder trust. Through a systematic literature review approach, this study identifies significant changes in modern audit practice, including the challenges of maintaining professional independence and integrity amid increasingly complex sustainability demands. The results show that in the post-modern era, auditors must adapt to more dynamic ethical standards, integrate social and environmental elements into their audits, and increase professional skepticism. The findings offer insights into the importance of ethics as a foundation in meeting sustainability challenges and provide a basis for further research to strengthen audit quality in the evolving digitalization era.